2006
DOI: 10.1021/nl052468b
|View full text |Cite
|
Sign up to set email alerts
|

Improved Subthreshold Slope in an InAs Nanowire Heterostructure Field-Effect Transistor

Abstract: An n-type InAs/InAsP heterostructure nanowire field-effect transistor has been fabricated and compared with a homogeneous InAs field-effect transistor. For the same device geometry, by introduction of the heterostructure, the threshold voltage is shifted 4 V, the maximum current on-off ratio is enhanced by a factor of 10,000, and the subthreshold swing is lowered by a factor 4 compared to the homogeneous transistor. At the same time, the drive current remains constant for a fixed gate overdrive. A single nanow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 12 publications
8
115
0
Order By: Relevance
“…One example is the GHz operation of InAs nanowire transistors [28] even when the quasi-dc characteristics exhibit hysteresis. [29] We now turn to data showing that surface states do not impede high fidelity transduction of biological/ionic signals.…”
Section: Below Instead Point To Hmentioning
confidence: 99%
“…One example is the GHz operation of InAs nanowire transistors [28] even when the quasi-dc characteristics exhibit hysteresis. [29] We now turn to data showing that surface states do not impede high fidelity transduction of biological/ionic signals.…”
Section: Below Instead Point To Hmentioning
confidence: 99%
“…The metallic CoSi 2 may serve as the source-drain contacts to the Si in the heterostructure; it is the first step to produce a nanoscale field-effect transistor. 30,31 We have selected Co and Si for our study since Co silicides possess very interesting and important properties. Single crystalline CoSi has ferromagnetic properties which were the focus of intensive research.…”
mentioning
confidence: 99%
“…A wide range of NW-based devices and systems, including transistors and circuits Huang, Duan, Cui, Lauhon, Kim & Lieber, 2001;Zhong et al, 2003), light emitters Wang et al, 2001;Huang, Mao, Feick, Yan, Wu, Kind, Weber, Russo & Yang, 2001;Duan et al, 2003), and sensors ) have been explored. NWFETs based on III-V (Dayeh, Soci, Yu, Yu & Wang, 2007;Dayeh, Aplin, Zhou, Yu, Yu & Wang, 2007;Bryllert et al, 2006;Lind et al, 2006;Thelander et al, 2004;Huang et al, 2005;) and II-VI (Goldberger et al, 2005;Ng et al, 2004) compound semiconductor materials have demonstrated promising FET characteristics in various gate geometries, namely, top-gate (Wang et al, 2004;2003), back-gate (Huang et al, 2005;Duan et al, 2001), wrap-around-gate (Ng et al, 2004;Bryllert et al, 2006), and core-shell structures. InSb and InAs NWs, in particular, are attractive candidates for NWFETs due to their high electron mobility at room temperature (Sze, 1981) and low contact resistance (Woodall et al, 1981).…”
Section: Background and Motivationmentioning
confidence: 99%
“…However, full band (FB) models are necessary to understand on-off current ratios and radio frequency (RF) power. Although there are series of reports on the experimental realizations of InSb and InAs NWFETs Ashley et al, 1997;Chau et al, 2005;Radosavljevic et al, 2008;Lind et al, 2006;Dayeh, Aplin, Zhou, Yu, Yu &Wang, 2007;Bryllert et al, 2006;Thelander et al, 2004;Ng et al, 2004), we find very few attempts to theoretically model them.…”
Section: Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation